PENGARUH PROMOSI DAN BRAND IMAGE TERHADAP KEPUTUSAN PEMBELIAN PRODUK SCARLETT PADA MARKETPLACE SHOPEE - Suyitno Suyitno; Yulie Wahyuningsih; Laily Agustin (Fakultas Ekonomi Universitas Islam Darul Ulum Lamongan, 2024)
There has been a significant increase in the level of public consumption of goods and services, with the transition of public spending from offline to online, because shopping online is easier, faster and cheaper. This study aims to determine the level of influence of promotions and brand image on purchasing decisions for Scarlett products on the Shopee marketplace. This study uses an explanatory method approach to explain the effect of promotion (X1) and brand image (X2) on purchasing decisions (Y). This study uses descriptive analysis techniques and Multiple Linear Regression Analysis. The number of samples in this study were 100 people. Samples were taken based on non-probability sampling with purposive sampling. Data collection techniques using primary data and secondary data. The results of this study indicate that promotion has a positive and significant effect on purchasing decisions for Scarlett products at the Shopee marketplace as evidenced by the t-count 4.183 > 1.984 t-table and a significance value of 0.000 <0.05; Brand image has a positive and significant effect on purchasing decisions for Scarlett products on the Shopee marketplace as evidenced by the t-count 8.016 > 1.984 t-table and a significance value of 0.000 <0.05; Promotion and brand image simultaneously influence purchasing decisions, as evidenced by the calculated F value of 95,715 > 3,939 F table and a significance value of 0.000 <0.05. The research results can be used by e-Commerce companies to optimize promotional media and build a brand image by maintaining service quality.